Estudo preliminar dos Diptera encontrados em lixo de 3 áreas urbanas do Município do Rio de Janeiro - Khouri, Andréa (1996)
Taxonomic study of Diptera found on organic garbage recently discarted by urban dwellers at three distinct areas of the city of Rio de Janeiro (Brazil): 1) an unoccupied lot, 2) a school, and 3) a hospital. The samples were collected once a month, from April 14th, 1992 to November 2nd, 1993, when 12.272 specimens were captured, with a specially adapted entomological net positioned over the garbage, in such way that the flies were traped by a apical partition of the net. All dipterans were identified to species, the majority being muscids and calliphorids. Seasonal specific distribution and sexual rate were statistically studied. The relative attraction exerted by garbage from different places was compared.